Waist Circumference as The Strongest Factor Related to Blood Glucose Level - Nenni Septyaningrum; Santi Martini (Universitas Airlangga, 2014)
Increased prevalence of overweight and obesity is associated with an increased incidence of type 2 Diabetes Mellitus (DM). Abdominal obesity is an important risk factor for the onset of DM. This study aims to determine the relationship between body mass index, abdominal circumference, and the ratio of hip waist circumference with blood sugar levels. The study design was cross-sectional. The study population was members of Integrated Health Posts for the elderly (Posyandu lansia) aged 45 to 70 years in the working area of the Public health center (PHC) of Menur registered in the Posyandu activities in May 2013. The number of respondents was 60 respondents taken using the simple random sampling method. The variables studied were respondent characteristics, body mass index, abdominal circumference, hip waist circumference ratio, and fasting blood sugar levels. The results showed that respondents were overweight (38%), obesity (33.3%), abdominal obesity based on abdominal circumference (77.8%), abdominal obesity based on the hip waist circumference ratio (81.7%), and blood sugar levels of125 mg/dl (8.3%). Pearson correlation test shows that body mass index has a relationship with blood sugar levels (p = 0.007; r = 0.345), abdominal circumference has a relationship with blood sugar levels (p = 0.001; r = 0.424,) and hip waist circumference ratio is related to blood sugar levels (p = 0.002;r = 0.392). The abdominal circumference has the strongest relationship with blood sugar levels. Abdominal circumference measurements should be used in elderly Posyandu activities to detect individuals at high risk of diabetes.